2019
DOI: 10.1634/theoncologist.2018-0711
|View full text |Cite
|
Sign up to set email alerts
|

What Is Important When Making Treatment Decisions in Metastatic Breast Cancer? A Qualitative Analysis of Decision-Making in Patients and Oncologists

Abstract: Background Metastatic breast cancer (MBC) is an ideal environment for shared decision‐making because of the large number of guideline‐based treatment options with similar efficacy but different toxicity profiles. This qualitative analysis describes patient and provider factors that influence decision‐making in treatment of MBC. Materials and Methods Patients and community oncologists completed in‐person interviews. Academic medical oncologists participated in focus groups. Interviews and focus groups were audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 28 publications
(39 reference statements)
3
50
0
1
Order By: Relevance
“…Results on interpersonal skills are in line with the literature, where understanding, empathy and relational versatility have been identified as relevant [44,45]. Desire for substantial engagement in decision-making has previously been demonstrated among breast cancer patients [46,47]. Furthermore, Schmidt and colleagues [2016], observed that preferences were not homogenous among lung cancer patients, and some subjects seemed to prefer a passive rather than an active role in decision-making [48].…”
Section: Discussionsupporting
confidence: 85%
“…Results on interpersonal skills are in line with the literature, where understanding, empathy and relational versatility have been identified as relevant [44,45]. Desire for substantial engagement in decision-making has previously been demonstrated among breast cancer patients [46,47]. Furthermore, Schmidt and colleagues [2016], observed that preferences were not homogenous among lung cancer patients, and some subjects seemed to prefer a passive rather than an active role in decision-making [48].…”
Section: Discussionsupporting
confidence: 85%
“…This led them to largely accept patient treatment preferences at face value and avoid providing information to balance preferences. This is especially pertinent because the priorities that inform patients' deliberations about treatments are rather different to those that inform the deliberations of oncologists and other practitioners [34]. Practitioner reluctance to explore patient treatment preferences seemed to reflect the belief that doing so is inconsistent with patient voluntariness, founded on an assumption that voluntariness depends on independent choice [35].…”
Section: Discussionmentioning
confidence: 99%
“…Other patient-related factors identified in this study have not been previously reported for VS, but have been investigated in other diseases. For example, personal characteristics, such as decision-making style and a patient's trust in the physician have been reported to influence treatment decisions in metastatic breast cancer [18]. The patient's cognitions about therapy and their own past experiences have been shown to influence management decisions in diabetes mellitus type II and lumbar disc herniation [19,20].…”
Section: Discussionmentioning
confidence: 99%